Isolasi dan Skrining Aktivitas Antimikroba Jamur Laut pada Alga Kappaphycus alvarezii dari Kabupaten Takalar Sulawesi selatan - Fitriana, Fitriana; Julianti, Elin; Wibowo, Marlia Singgih (Jurnal Farmasi Indonesia, 2016)
Marine microorganisms, especially actinomycetes bacteria and fungi produce a variety of secondary metabolites that biologically active and have a unique structure. This study aims to isolate some strains of marine fungi that grow on marine algae as a potential source of antimicrobial agent. Marine fungal strains isolated from the marine algae with antimicrobial activity screening is done by using the disc diffusion method. In this study, it was obtained 18 strains of fungal isolates. The screening results that give best antimicrobial activity shown by the activity of the extract liquid culture of fungal isolate strain AKT.C6 are 10.0 mm against the bacteria Escherichia coli and 10.8 mm against Bacillus subtilis. Mycelium extract of fungal isolates strain AKT.C4 is 16.9 mm against the bacteria Escherichia coli and 17.6 mm against Bacillus subtilis, while the liquid culture extract and mycelium extract did not show any activity against Candida albicans. The isolation of fungi from Kappaphycus alvarezii algaee has potential as an antibacterial agent.